Storage Construction, Fruits and Vegetables - Flores, Rolando A.; Gast, Karen L. B. (My University, 1992)
This publication describes the postharvest management of commercial horticultural crops.
MF1039_1992_06
Keywords: MF1039; Crops; Fruits and Vegetables; Equipment and Structures; MF